Modeling the Impact of Traveling Time on the Utilization of Maternity Services Using Routine Health Facility Data in Siaya County, Western Kenya - Oluoch, Felix; Ayodo, George; Owino, Fredrick; Okuto, Erick (American Journal of Geographic Information System, 2020)
In Kenya, no studies have attempted to use routine health facility data disaggregated by level of care, to find out if there is a significant statistical relationship between physical accessibility and utilization of maternity services at the ward administrative level. A cross-sectional study design used publicly available geospatial data in combination with routine data from the web-based district health information software (DHIS2) platform. Access Mod (version 5.2.6) was used for travelling time analysis. ArcGIS (version 10.5) and R (version 3.5.3) sufficed for the preparation of geospatial input and the manipulation of Access Mod results respectively. The associations between the independent and dependable outcome was computed using a Zero-inflated Poisson regression model at 95% confidence level. The findings in Siaya County revealed a higher likelihood of a skilled delivery 35% (0.353; CI: 0.349–0.357) and 16% (0.164; CI: 0.162–0.167) respectively, for every unit increase in the proportion of pregnant women who could reach a hospital and health centre within an hour of walking, as compared to being within an hour of a dispensary 4.6% (0.046; CI: 0.045–0.048) using motorcycle transport. Simply advising women to opt for motorized transportation schemes to improve their access to low quality facilities, may in fact, result in diminishing returns. The immediate implication is that policy makers need to upgrade lower tier maternity health services in Siaya County, as pregnant women may value quality of services regardless of the distance. Future research should consider looking at the relationship between skilled delivery and the capacity of existing maternity health services.
Keywords: Maternity services; Geographic information systems